Synthesis, Antibacterial Evaluation and QSAR of α-Substituted-N4-Acetamides of Ciprofloxacin and Norfloxacin - Amjad M. Qandil; Lorca O. Al-Zoubi; Amal G. Al-Bakri; Haneen A. Amawi; Qosay A. Al-Balas; Abdulmalik M. Alkatheri; Abdulkareem M. Albekairy (MDPI AG, 2014)
Twenty six α-substituted N4-acetamide derivatives of ciprofloxacin (CIPRO) and norfloxacin (NOR) were synthesized and assayed for antibacterial activity against Pseudomonas aeruginosa, Escherichia coli, Staphylococcus aureus and Bacillus subtilis. The derivatives were primarily more active against Gram-positive bacteria. The CIPRO derivatives, CD-7 (Ar = 3-chlorophenyl), CD-9 (Ar = 2-pyrimidyl) and CD-10 (α-phenyl, Ar = 2-pyrimidyl), exhibited lower MIC values, 0.4-0.9 μM, against Staphylococcus aureus than CIPRO, while only compound CD-10 exhibited better activity, 0.1 μM, against Bacillus subtilis than CIPRO. In addition, compounds CD-5 (Ar = 2-methoxyphenyl), CD-6 (α-phenyl, Ar = 2-methoxyphenyl), CD-7 (Ar = 3-Chlorophenyl), CD-8 (α-phenyl, Ar = 3-chlorophenyl) and CD-9 (Ar = 2-pyrimidyl) showed MIC values below 1.0 μM against this strain. The NOR derivatives showed lower activity than NOR itself against Staphylococcus aureus, although ND-6 (α-phenyl, Ar = 2-methoxyphenyl) and ND-7 (Ar = 3-chlorophenyl) showed MIC values less than 2 μM. Two NOR derivatives, ND-7 and ND-6, exhibited MIC values of 0.7 and 0.6, respectively, which were comparable to that of NOR against Bacillus subtilis, while compounds ND-8 (α-phenyl, Ar = 3-chlorophenyl) and ND-10 (α-phenyl, Ar = 2-pyrimidyl) exhibited MIC values less than 1.0 μM against the same strain. QSAR revealed that while polarity is the major contributing factor in the potency against Staphylococcus aureus, it is balanced by lipophilicity and electron density around the acetamide group. On the other hand, electron density around the introduced acetamide group is the major determining factor in the activity against Bacillus subtilis, with a lesser and variable effect for lipophilicity.